Mechanisms of Memory Dysfunction during High Altitude Hypoxia Training in Military Aircrew. (7th December 2016) - Nation, Daniel A.; Bondi, Mark W.; Gayles, Ellis; Delis, Dean C.
Abstract: Objectives: Cognitive dysfunction from high altitude exposure is a major cause of civilian and military air disasters. Pilot training improves recognition of the early symptoms of altitude exposure so that countermeasures may be taken before loss of consciousness. Little is known regarding the nature of cognitive impairments manifesting within this critical window when life-saving measures may still be taken. Prior studies evaluating cognition during high altitude simulation have predominantly focused on measures of reaction time and other basic attention or motor processes. Memory encoding, retention, and retrieval represent critical cognitive functions that may be vulnerable to acute hypoxic/ischemic events and could play a major role in survival of air emergencies, yet these processes have not been studied in the context of high altitude simulation training.Methods: In a series of experiments, military aircrew underwent neuropsychological testing before, during, and after brief (15 min) exposure to high altitude simulation (20, 000 ft) in a pressure-controlled chamber.Results: Acute exposure to high altitude simulation caused rapid impairment in learning and memory with relative preservation of basic visual and auditory attention. Memory dysfunction was predominantly characterized by deficiencies in memory encoding, as memory for information learned during high altitude exposure did not improve after washout at sea level. Retrieval and retention of memories learned shortly before altitude exposure were also impaired, suggesting further impairment in memory retention.Conclusions: Deficits in memory encoding and retention are rapidly induced upon exposure to high altitude, an effect that could impact life-saving situational awareness and response. ( JINS, 2017, 23, 1–10)